PERANCANGAN POSTER “STOP KECURANGAN UJIAN NASIONAL” - Hendra Rotama (Besaung : Jurnal Seni Desain dan Budaya, 2017)
National Examination is a national evaluation system of education by stipulating the educational standard that aims to mapping educational issues in order to formulate the national education policy. However, in the organizers found many acts that injure education itself. The national examination is one of the government's policies in education that is used to improve the quality of education of the nation. Implementation of national examinations accompanied by honesty, objectivity and justice can serve as a tool to improve the quality of human resources. To convey a visual information to the target audience, consideration is required in order to realize the desired visual. In this design, the teacher becomes the visual object to be communicated, because the teacher is a reflection of education itself. The object of the teacher symbolized by the work uniform will be easily understood by the common people.Key words : Design, Poster, Design